Right ventricular end‐diastolic volume and outcomes in exacerbations of COPD. Issue 1 (25th October 2021) - Leong, Paul; Osadnik, Christian R.; King, Paul T.; MacDonald, Martin I.; Ko, Brian S.; Lau, Kenneth K.; Joosten, Simon A.; Kathriachchige, Gayan; Chua, Alexander; Hamza, Kais; Kuganesan, Ahilan; Troupis, John M.; et al.
Abstract: Background and objective: Right ventricular (RV) volumes are crucial outcome determinants in pulmonary diseases. Little is known about the associations of RV volumes during hospitalized acute exacerbations of chronic obstructive pulmonary disease (AECOPD). We aimed to ascertain associations of RV end‐diastolic volume indexed to body surface area (RVEDVI) during hospitalized AECOPD and its relationship with mortality in long‐term follow‐up. Methods: This is a prospective observational cohort study (December 2013–November 2019, ACTRN12617001562369) using dynamic retrospective ECG‐gated computed tomography during hospitalized AECOPD. RVEDVI was defined as normal or high using Framingham Offspring Cohort values. Cox regression determined the prognostic relevance of RVEDVI for death. Results: A total of 148 participants (70 ± 10 years [mean ± SD], 88 [59%] men) were included, of whom 75 (51%) had high RVEDVI. This was associated with more frequent hospital admissions in the 12 months before admission (52/75 [69%] vs. 38/73 [52%], p = 0.04) and higher breathlessness (modified Medical Research Council score, 2.9 ± 1.3 vs. 2.4 ± 1.2, p = 0.007). During follow‐up, high RVEDVI was associated with greater mortality (log‐rank p = 0.001). In univariable Cox regression, increasing RVEDVI was associated with higher mortality (hazard ratio [HR]: 1.02 per ml/m 2 ; 95% CI: 1.01, 1.03; p = 0.001). In multivariable Cox regression, RVEDVI was independently associated with mortality (HR: 1.01 per ml/m 2 ; 95% CI: 1.00, 1.03; p = 0.050) at a borderline significance level. Adding RVEDVI to three COPD mortality prediction systems improved model fit (pooled chi‐square test [BODE: p = 0.05, ADO: p = 0.04, DOSE: p = 0.02]). Conclusion: In patients with hospitalized AECOPD, higher RV end‐diastolic volume was associated with worse acute clinical parameters and greater mortality. Abstract : In a prospective cohort study of 148 individuals with hospitalized chronic obstructive pulmonary disease exacerbations, high right ventricular end‐diastolic volume on dynamic computed tomography was associated with adverse acute markers and long‐term mortality. See related Editorial